Co-assembled Glycyrrhiza nanoparticles embedded supramolecular protein hydrogels to enhance licochalcone A release for acute inflammation management - Zhuxian Wang; Jun Liu; Yufan Wu; Yamei Li; Hongxia Zhu; Qiang Liu; Bin Yang (International Journal of Pharmaceutics: X)
Licochalcone A (LA) garnered remarkable acclaim in acute inflammation therapy, however, poor release capability from the matrix and oral bioavailability restrict its oral delivery. To address this challenge, licorice-derived glycyrrhizic acid (GA) and LA were co-assembled into GA-LA (GLA) binary co-assembled Glycyrrhiza nanoparticles (BCGNs), which were subsequently incorporated into supramolecular hydrogel matrix. GLA BCGNs demonstrated a remarkable capacity to scavenge various reactive oxygen species (ROS) and facilitated the cascade process of O2•−-H2O2-O2 in vitro. Subsequently, GLA was dispersed in nano form into ovalbumin (OVA) and rhamnose (Rha) solutions, which were next self-assembled into OVA-Rha-GLA hydrogels. Remarkably, the introduction of Rha induced disordered secondary conformation of OVA, which decreased its mechanical properties and inherent binding energy, thereby shaping the three-dimensional supramolecular spatial structures of OVA-Rha-GLA networks. The assembly mechanisms indicated that the hydrogen bonding predominantly drove the assembly of loose supramolecular networks surrounded by -OH, -CH2 and CO bonds on the Rha and OVA. Notably, the conformational transformation facilitated faster LA release, confirmed by computational simulation analysis, which was conducive to acute inflammation curation. Therefore, OVA-Rha-GLA exhibited excellent anti-inflammation and ROS-scavenging versatilities, displaying improved oral bioavailability compared to hydrogels lacking BCGNs or Rha in cellular and animal acute inflammation experiments. The results provided novel BCGNs-embedded supramolecular hydrogel systems to improve the drug release and anti-inflammatory bioactivities of LA, which demonstrated great promise in the management of acute inflammation.